Improving learning outcomes: The effectiveness of e-book reading literacy based in learning management psychology - Jasrial Jasrial; Andra Saputra; Rifma Rifma (Jurnal Cakrawala Pendidikan, 2023)
The research aims to improve learning outcomes of Management Psychology Courses use E-book teaching material reading literacy based for the student of the Education Administration Study Program, Faculty of Education, Universitas Negeri Padang, Indonesia. The research used 2 x 2 factorial design experimental methods with ANOVA. The research obtained the highest score 96.6 for experimental class, and 93.3 for control class. The students learning outcomes in the experimental class have an average 81.93 and average 71.75 for control class. The result of t-test for both of class, tcount was 5.11 and ttable was 1.66. It implied there was a significant difference about students learning outcomes. The learning outcomes of student that used E-book teaching material was higher than students that used printed teaching materials. The students who have high reading literacy and used E-book teaching material, the student learning outcomes was higher than the student who have high reading literacy but used printed materials. And the students who have low reading literacy and used E-book teaching material, the learning outcomes was higher than the students who have low reading literacy but used printed teaching material.